The efficacy and safety of Gukang Capsule for primary osteoporosis: a systematic review and meta-analysis of randomized clinical trial - Wei, Zhenpu; Wang, Zhiqiang; Huang, Yunmei; Chen, Xuzheng; Sun, Pan; Zhang, Chutian; Zhou, Fen; Lin, Yanping (Frontiers in Pharmacology, 2024)
Background: Gukang Capsule is employed in China as a form of complementary and alternative medicine (CAM) for the treatment of primary osteoporosis (POP). The primary aim of this study was to assess the clinical effectiveness and safety of Gukang Capsule in the treatment of POP.Methods: A systematic search was conducted across multiple academic databases including PubMed, Cochrane Library, China National Knowledge Infrastructure, Chongqing VIP Information, and Wanfang database to identify randomized controlled trials investigating the Gukang Capsule in the treatment of POP. The screening process, data extraction, and assessment of methodological quality were carried out independently by two reviewers. Statistical analysis was conducted utilizing Rev Man 5.3 software. Subgroup analysis was performed based on the combination of OPF. Subgroup analysis was performed according to whether OPF were combined. Stata 12.0 was used for sensitivity and bias analysis.Results: Nineteen studies were assessed that included 1804 participants. The results showed that compared with the control group, the total effective rate (RR=1.26, 95% CI, 1.20, 1.33), the Medical Outcomes Study Short-form 36 [RR=1.26, 95% CI(1.20, 1.33)], the bone mineral density (BMD) of lumbar vertebra (SMD=0.77, 95% CI, 0.48, 1.07), the BMD of femoral neck [SMD=0.84, 95% CI(0.53, 1.14)], and the BMD of Ward's triangle (SMD=0.64, 95% CI, 0.44, 0.85) of the Gukang Capsule experimental group were higher. Compared with the control group, the fracture healing time (SMD=-2.14, 95% CI, -2.45, -1.84), the bone specific alkaline phosphatase (BALP) levels in serum (SMD=-2.00, 95% CI, -2.83, -1.17), the tartrate resistant acid phosphatase 5b (TRACP-5b) levels in serum (SMD=-2.58, 95% CI, -3.87, -1.29) of the Gukang Capsule experimental group were lower. The bone glaprotein (BGP) levels in serum (SMD=-0.22, 95% CI, -1.86, 1.43) and the adverse events (RR=0.80, 95% CI, 0.40, 1.63) of the experimental group and the control group have no difference. Conclusions: Gukang Capsule, as a CAM for the management of POP, exhibits the potential to enhance BMD and quality of life, expedite the healing time of OPF, diminish levels of BALP and TRACP-5b, and improve the total effective rate without increasing the adverse events.